2020
DOI: 10.1016/j.ejim.2020.05.043
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: The Waterloo of governments, healthcare systems, and large health organizations

Abstract: The Waterloo of governments, healthcare systems, and large health organizations To the editor In our humble opinion, the current corona-virus disease 2019 (COVID-19) crisis presents the modern Waterloo of western authorities at multiple levels, both at the administrative, the scientific, and the social level. The aim of this letter to the editor is not to engage into a blame game; it is to highlight several black boxes in order to be avoided by rather unaffected countries or during the case of a second wave of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The ongoing Coronavirus Disease 19 (COVID-19) pandemic caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has affected so far 218 countries with over 94 million cases, about 2 million deaths and over 67 million recovered ( 1 ), with dramatic effects on communities and healthcare systems ( 2 ). The beginning of mass vaccination campaigns in late 2020 in the USA and the UK, and from early 2021 in other countries, will help controlling the infection spread and limiting its consequences, also providing indirect protection to non-vaccinated individuals through the mechanism of “herd immunity” ( 3 , 4 , 5 ).…”
mentioning
confidence: 99%
“…The ongoing Coronavirus Disease 19 (COVID-19) pandemic caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has affected so far 218 countries with over 94 million cases, about 2 million deaths and over 67 million recovered ( 1 ), with dramatic effects on communities and healthcare systems ( 2 ). The beginning of mass vaccination campaigns in late 2020 in the USA and the UK, and from early 2021 in other countries, will help controlling the infection spread and limiting its consequences, also providing indirect protection to non-vaccinated individuals through the mechanism of “herd immunity” ( 3 , 4 , 5 ).…”
mentioning
confidence: 99%
“…It seems that Chinese HCWs reported worse mental health being the first to suddenly be faced with an unknown and highly contagious virus. Healthcare systems and HCWs had to struggle with the rapid spread of the Coronavirus and the unprecedented number of deaths, also within healthcare systems that appear not to have been prepared for this pandemic (Doumas et al, 2020). The rapid increase of infected patients and the uncertainty of transmission in the early stage of the outbreak increased the enormous workload and psychological burden of medical workers (Q.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that EMS calls forecast the ICU admission trend more than the actual number of people tested positive; given the mentioned considerations, this does not come as a surprise. Actually, it should be considered as a point of interest in this research, since COVID clinical presentation has been switching in the past few months, and the main focus (from a public health perspective) is still on its impact on health structures and systems, whose resilience has been heavily tested in the last two years [37,38]. A growing amount of positive, yet asymptomatic or mildly symptomatic cases, is of little interest when compared to the warnings of a possible imminent surge in ICU demand: in such scenarios, EMS calls analysis, alone or in combination with other indicators, can be useful in health programming on a short-time period, and on a local level.…”
Section: Limitationsmentioning
confidence: 99%